2016
DOI: 10.1186/s13075-016-1052-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of baseline gene expression signatures predicting therapeutic responses to three biologic agents in rheumatoid arthritis: a retrospective observational study

Abstract: BackgroundAccording to EULAR recommendations, biologic DMARDs (bDMARDs) such as tumor necrosis factor inhibitor, tocilizumab (TCZ), and abatacept (ABT) are in parallel when prescribing to rheumatoid arthritis (RA) patients who have shown insufficient response to conventional synthetic DMARDs. However, most prediction studies of therapeutic response to bDMARDs using gene expression profiles were focused on a single bDMARD, and consideration of the results from the perspective of RA pathophysiology was insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…The primary objective of this study was to identify novel molecules associated with therapeutic responses to ABA for patients with RA, and the secondary objective was validation of the results of the previous study [9]. Fisher's exact test and Student's t test were used to compare the categorical and continuous variables between two groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary objective of this study was to identify novel molecules associated with therapeutic responses to ABA for patients with RA, and the secondary objective was validation of the results of the previous study [9]. Fisher's exact test and Student's t test were used to compare the categorical and continuous variables between two groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The GO analysis of the 392 genes downregulated in the responders did not identify a specific group of genes. The previously reported genes associated with therapeutic response to ABA, which were elongation arrest and recovery-related genes and CD56-specifically expressed genes [9], were not included in the over-or under-expressed genes.…”
Section: Genes Associated With Clinical Response To Aba Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we also do not know which of the available antiinflammatory strategies, alone or in combination, will have the best therapeutic potential. Activity of select inflammatory pathways among different patients may affect therapeutic responsiveness to specific interventions (116). Additionally, the more recently introduced biological agents are narrowly focused on very specific targets, whereas older antiinflammatory agents such as salicylate or methotrexate may have broader effects (see below).…”
Section: Pharmacologic Approaches That Directly Target Inflammationmentioning
confidence: 99%
“…Transcriptional profiles that can be used to monitor disease development or predict response to treatment would be valuable for developing personalized therapies for autoimmune diseases. Multiple studies have attempted to identify signatures that can clinically stratify patients for this purpose . A recent study, for example, showed that the IFN‐stimulated genes associated with SLE were markedly different between populations of European ancestry and those of East Asian ancestry .…”
Section: Discussionmentioning
confidence: 99%